Dacochordodes Bacescui Capuse, 1966: Report of the First Two Isolations from Humans - Zoran P Pikula; Sergei E Spiridonov; Ednar T Drljevic (Canadian Journal of Infectious Diseases)
This report describes two cases of isolation of Dacochordodes bacescui Capuse, 1966 from human intestinal infections. In the first case, two adult worms were identified in the vomitus of a man suffering from abdominal pain and nausea. In the second case, a worm was passed in the stool of a woman suffering from abdominal pain and pruritus. Human gastrointestinal infection with this parasite has not previously been reported.